Pengaruh Social Influence dan Hedonic Shopping Motivation terhadap Impulsive Buying Behavior pada Generasi Z dengan Financial Literacy sebagai Variabel Moderasi - Faujiah, Fuji; Afriza, Edi Fitriana; Srigustini, Astri (HATTA : Jurnal Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The rapid development of e-commerce and social media has encouraged the emergence of impulsive buying behavior, especially among students. Social factors and hedonic shopping motivation are thought to be the main triggers in making unplanned purchasing decisions. This study aims to analyze the effect of social influence and hedonic shopping motivation on impulsive buying behavior with financial literacy as a moderating variable in students of Departemenet of Management Class of 2024, Nusa Putra University. This research uses a quantitative approach with a survey mwthod. The sample consisted of 105 respondents selected using purposive sampling technique. Data collection was carried out through distributing questionnaires, and analyzed using SPSS software version 25. The results showed that social influence, hedonic shopping motivation had a positive and significant effect on impulsive buying behavior. Meanwhile, financial literacy does not moderate the influence of social influence and hedonic shopping motivation on impulsive buying behavior in Generation Z Manaement Departement Studendent Class of 2024.